Dual Languaging as Strategy and Translanguaging as Tactic in Two-Way Dual Language Programs. Issue 2 (3rd April 2019) - Somerville, Jessica; Faltis, Christian
Abstract : In this article we draw on translanguaging theory and notions of strategies and tactics as a way to understand what we refer to as dual languaging in the context of TWDL schooling. We provide examples of dual languaging practices in fourth-grade math and social studies lessons that took place in a Spanish-English TWDL elementary school located in a large Midwestern city. We propose that the children's use of dual languaging practices was a tactic shaped by and in response to the TWDL model. We argue that it is important for educators to understand: (a) how the notion of Spanish and English as separate languages in TWDL oversimplifies students' and teachers' actual languaging practices, and (b) how the language distribution model in TWDL schools can shape the languaging tactics and strategies taken up by children and their teachers.